Monetary Policy as a Driver of Credit Expansion and Deposit Mobilization in Banks: Case Study in Iraqi Commercial Banks - Hasan, Barham Bakr; Vladimirovich, Girinsky Andrey; Mahmud, Mahmud Hedi Khalid (Unisia, 2025)
This study explores how monetary policy influences credit growth and deposit mobilization in Iraqi commercial banks. It looks at how central banks use tools like interest rates, reserve requirements, and open market operations to control credit availability and attract deposits. In Iraq’s developing economy, where oil plays a key role, these policies are especially important. However, the banking sector in Iraq faces several challenges, including vulnerability to external factors and the presence of informal financial systems. This research aims to provide a clear understanding of how monetary policy has functioned over time and how it could contribute to greater economic stability and growth. The findings suggest that while monetary policy can have a strong impact on credit and deposit activity, its full potential is often limited by weaknesses in the banking system.